2018
DOI: 10.1097/pcc.0000000000001660
|View full text |Cite
|
Sign up to set email alerts
|

Venoarterial Extracorporeal Membrane Oxygenation Versus Conventional Therapy in Severe Pediatric Septic Shock*

Abstract: The use of venoarterial extracorporeal membrane oxygenation in severe pediatric sepsis is not by itself associated with improved survival. However, venoarterial extracorporeal membrane oxygenation significantly reduces mortality after cardiac arrest due to septic shock. Venoarterial extracorporeal membrane oxygenation flows greater than 150 mL/kg/min are associated with almost twice the survival rate of conventional therapy or standard-flow extracorporeal membrane oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…The most recent and largest report of venoarterial ECMO in 44 pediatric patients with RSS secondary to bacterial, viral, or fungal infection admitted to seven tertiary PICUs across five different countries compared their outcome to 120 children with RSS managed by conventional therapy [488]. Inclusion in the study required children to meet three of four criteria for severe septic shock in the first 24 h of their ICU stay: arterial pH less than or equal to 7.15, arterial lactate greater than or equal to 4.0 mmol/L, base excess less than or equal to -10 mmol/L, and in-hospital cardiac arrest.…”
mentioning
confidence: 99%
“…The most recent and largest report of venoarterial ECMO in 44 pediatric patients with RSS secondary to bacterial, viral, or fungal infection admitted to seven tertiary PICUs across five different countries compared their outcome to 120 children with RSS managed by conventional therapy [488]. Inclusion in the study required children to meet three of four criteria for severe septic shock in the first 24 h of their ICU stay: arterial pH less than or equal to 7.15, arterial lactate greater than or equal to 4.0 mmol/L, base excess less than or equal to -10 mmol/L, and in-hospital cardiac arrest.…”
mentioning
confidence: 99%
“…In a multicenter study of children supported with ECMO for septic shock, VA-ECMO showed beneficial effect for children with a cardiac arrest and ECMO flows over 150 ml/kg/min were associated with higher survival compared to "standard" flows (survival 82 vs. 43%) (56).…”
Section: Adequacy Of Ecmo Blood Flowmentioning
confidence: 94%
“…An ELSO review by Polito identified cardiac arrest and lower pH at ECMO initiation risk factors for neurological complications in neonates (cerebral hemorrhage, infarction, seizures, and brain death) (49). Several other pediatric series highlight the weight of pre-ECMO lactate on ECMO survival (18,56,57). Close collaboration with neonatologists and open discussion about local protocols and indications/inclusion criteria for ECMO could reduce the delay between clinical presentation and ECMO cannulation, and therefore improve outcomes.…”
Section: Future Directions Earlier Use Of Ecmo With Better Technologymentioning
confidence: 99%
“…We were surprised by the benefit brought by central cannulation on survival in the multivariate analysis (p = 0.046) while higher flows did not reach significance on survival nor in the uni-(p = 0.27) nor in the multivariate analyses (p = NS). Other studies in paediatric septic shock have shown a survival benefit from ECMO flow rates greater than 150 ml/kg/min [2].…”
mentioning
confidence: 93%
“…Accurate and rapid assessment can improve the timeliness of cannulation. Although the highest ECMO benefit was observed in children post-cardiac arrest, clinicians should endeavour to recognize impending cardiac arrest prior to its occurrence [2]. In summary, although decisions on whether to place a child with sepsis on ECMO may always happen on an individual basis, such should not prevent us from applying benefit threshold estimates to assess the appropriateness of such decisions-similar to most areas of critical care where risk-adjusted benchmarking has been the standard for decades [9].…”
mentioning
confidence: 99%